2021
DOI: 10.1038/s41598-021-89700-8
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of mental health issues among the general population during the coronavirus disease-2019 pandemic: a systematic review and meta-analysis

Abstract: To provide a contemporary global prevalence of mental health issues among the general population amid the coronavirus disease-2019 (COVID-19) pandemic. We searched electronic databases, preprint databases, grey literature, and unpublished studies from January 1, 2020, to June 16, 2020 (updated on July 11, 2020), with no language restrictions. Observational studies using validated measurement tools and reporting data on mental health issues among the general population were screened to identify all relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
364
1
30

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(414 citation statements)
references
References 144 publications
(173 reference statements)
19
364
1
30
Order By: Relevance
“…It seems plausible that the information-seeking about the pandemic during lockdowns would also have taken place in the context of more TSPC, especially since face-to-face interactions were limited. In addition, the correlation between perceived stress and all research variables is in line with the previous findings mentioned in a metaanalysis [81] that focused on the increasing global prevalence of mental health issues among the general population during the COVID-19 pandemic, such as stress, depression and anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…It seems plausible that the information-seeking about the pandemic during lockdowns would also have taken place in the context of more TSPC, especially since face-to-face interactions were limited. In addition, the correlation between perceived stress and all research variables is in line with the previous findings mentioned in a metaanalysis [81] that focused on the increasing global prevalence of mental health issues among the general population during the COVID-19 pandemic, such as stress, depression and anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…Our results are congruent with research showing higher anxiety rates than the general population 33 , 40 , 58 . Additionally, a recent systematic review of global prevalence of mental health issues in the general population showed prevalences of stress, depression, and anxiety, at 36.50%, 28.00%, and 26.90%, respectively 59 . In our study, students reported almost twice as high stress and depression levels.…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, identifying risk factors associated with psychological distress is critically important for policymakers to design interventions that can effectively mitigate deteriorating mental health conditions. An increasing number of studies have demonstrated that the psychological distress is increasing during the COVID-19 pandemic, 8 and that the underlying reasons are different before and during the pandemic. 9 10 Research has found that those who are vulnerable to financial stressors (eg, lowincome levels or unemployed) are more likely to experience psychological distress during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%